2021
DOI: 10.1002/jor.25117
|View full text |Cite
|
Sign up to set email alerts
|

Gait asymmetries are exacerbated at faster walking speeds in individuals with acute anterior cruciate ligament reconstruction

Abstract: Previous research suggests more biomechanically demanding tasks (e.g., stair descent, hopping) magnify biomechanical asymmetries compared with walking after anterior cruciate ligament (ACL) reconstruction. However, it is unclear if modifying task‐specific constraints, like walking speed also elicits greater biomechanical asymmetries in this population. We examined the effects of manipulating walking speed on ground reaction force (GRF) asymmetries in individuals with ACL reconstruction and uninjured controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…This finding is consistent with prior studies that have shown that increasing task difficulty exacerbates the differences in knee biomechanics for individuals with an ACL reconstruction. 7,26,27 Interestingly, biomechanical changes observed during a difficult task (eg, stair climbing) have been linked to patient-reported outcomes for individuals with ACL reconstruction. 40 Hence, we encourage future studies to examine potential differential effects in muscle force by increasing the difficulty in a variety of tasks, which may serve as useful clinical tools to better detect residual force deficits and track recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with prior studies that have shown that increasing task difficulty exacerbates the differences in knee biomechanics for individuals with an ACL reconstruction. 7,26,27 Interestingly, biomechanical changes observed during a difficult task (eg, stair climbing) have been linked to patient-reported outcomes for individuals with ACL reconstruction. 40 Hence, we encourage future studies to examine potential differential effects in muscle force by increasing the difficulty in a variety of tasks, which may serve as useful clinical tools to better detect residual force deficits and track recovery.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Task difficulty is also an important factor to consider when designing studies, as important between-group differences may only appear when a locomotor task is sufficiently difficult. [23][24][25] Increasing the difficulty of locomotor tasks can magnify kinematic and kinetic differences between ACLR and healthy knees, 5,26,27 likely due to the deficits in the ability to increase muscle forces and activation levels to meet the increase in mechanical loading of the knee during biomechanically challenging tasks. 28,29 For example, we previously found that individuals with an ACL reconstruction exhibited significantly lower peak knee flexion moments than controls when descending stairs, a difference we did not detect during overground level walking.…”
mentioning
confidence: 99%
“…The upscaled trajectories acted as a target for participants to achieve while they walked and was used to ensure that participants were encouraged to increase range of motion during training. The 80% walking speed was used to promote a more symmetrical gait pattern and allow for greater loading of the leg muscles (31). At each training session, participants were reminded to match the target as closely as possible and were cued to do so when necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have explored the effects of walking speed on the gait asymmetries of ACL-deficient subjects ( Tibone et al, 1986 ; Stergiou et al, 2004 ; Fuentes et al, 2011 ; Yim et al, 2015 ; Nazary-Moghadam et al, 2019 ; Stoelben et al, 2019 ; Garcia et al, 2021 ). Nazary-Moghadam et al found that fast walking speeds can significantly decrease flexion-extension Lyapunov Exponent (a functional stability parameter) in ACLD patients compared to healthy controls ( Nazary-Moghadam et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Walking fast is highly demanding concerning knee function. It was reported that walking as fast as healthy controls may reveal gait asymmetries and functional disorders among patients with ACLD ( Tibone et al, 1986 ; Fuentes et al, 2011 ; Garcia et al, 2021 ). It is also possible that additional knee kinematic asymmetries could be revealed among ACLD patients when they are walking fast.…”
Section: Introductionmentioning
confidence: 99%